Employment prospects in the Irish popular music industry - Burke, Andrew E. (Statistical and Social Inquiry Society of Ireland, 1995)
The paper conducts a statistical analysis of employment in the Irish pop music industry. In the absence of official data, the paper collects and manipulates new data sets on the industry. The analysis confirms that there has been a dramatic growth in employment in the industry, the overwhelming majority of which has occurred among musicians and composers (artists). The research also finds tentative evidence to suggest that the artist sector has been the main engine of growth for the Irish music industry as a whole. On this basis the paper then researches the employment prospects of artists. The paper finds that employment in the artist sector of the industry does not appear to offer serious job creation prospects. Most of the employment among artists is found to be precarious, low wage and of short duration. The paper, therefore, argues that employment training schemes for musicians are not economically feasible. The paper concludes that if employment in the music industry is to increase, it must occur in activities outside of the artist sector.
Read before the Society, 26 January 1995
Keywords: Music industry; Employment prospects; Artist's income; Music; 314.15